Technological research in the development of a cosmetic product for acne correction during and after retinoid treatment - Tymochko, Alina; Barna , Oksana; Plaskonis , Yuliya; Hrytsyshyn, Liliia (The Ukrainian Scientific Medical Youth Journal, 2025)
аcne is a common dermatological problem significantly affecting patients' quality of life. Retinoids are among the effective treatments, known for their pronounced therapeutic effect. However, prolonged retinoid use is accompanied by side effects such as dryness, redness, irritation, peeling skin, and increased sensitivity to external factors. Cosmetic products with various actions are widely used to minimize these negative manifestations but often only partially compensate for therapy side effects. Therefore, developing a cosmetic product that comprehensively addresses negative skin reactions during and after retinoid treatment remains relevant. Our goal was to investigate the influence of pharmaceutical factors on quality and effectiveness indicators of a cosmetic product in the form of an emulgel for home skincare during and after retinoid acne treatment. An optimal cosmetic product formulation, specifically an emulgel combining emulsion and gel properties, was selected to provide effective moisturizing, nourishment, and skin barrier protection. The study of cosmetic product samples revealed that all tested samples exhibited satisfactory organoleptic properties, with a pH range of 6,73 to 7,11. According to the homogeneity and dispersity analysis, the least stable and most heterogeneous were samples 5 and 9, which demonstrated a diluted structure, significant gaps between particles, and signs of potential phase separation. Evaluation of colloidal stability showed that all tested samples were stable. However, thermodynamic stability testing revealed separation in samples 5 and 6. The best results for spreadability were observed in samples 2, 4, and 8, which showed good distribution ability and effective application during testing. 9 batches of the emulgel were produced, incorporating selected excipients and active ingredients, including plant oils, hydrophilic moisturizers, antioxidants, vitamins, and anti-inflammatory components promoting skin regeneration and reducing irritation. Samples underwent evaluations for organoleptic characteristics, pH, thermostability, colloidal stability, homogeneity, and dispersibility via microscopy. Emulsion type identification was conducted using dye staining. Three batches exhibited satisfactory pharmaceutical-technological properties: batch 2 with 0.5% guar gum solution, batch 4 with 1% sodium alginate solution, and batch 8 with 0.5% high molecular weight sodium hyaluronate solution. Further studies are planned to investigate the consumer characteristics of the selected cosmetic cream samples in order to choose the optimal emulgel composition for home care during retinoid treatment.